Evaluation of the use of video consultation in German rheumatology care before and during the COVID-19 pandemic - Richter, Jutta G.; Chehab, Gamal; Reiter, Joana; Aries, Peer; Muehlensiepen, Felix; Welcker, Martin; Acar, Hasan; Voormann, Anna; Schneider, Matthias; Specker, Christof (Frontiers in Medicine, 2022)
Background The COVID-19 pandemic led to transformations in healthcare infrastructures and increased use of (innovative) telemedicine (TM) tools. Comparison of the use of video consultation (VC) in rheumatology in the pre-pandemic period and during the pandemic might allow for evaluating this new form of consultancy in healthcare due to changing conditions and possibilities. Materials and methods Cross-sectional nationwide online survey among German rheumatologists and rheumatologists in training between March and May 2021 promoted by newsletters and Twitter posts. Results Results refer to 205 participants. The majority was male (59%), older than 40 years (90%). Thirty-eight percent stated to have employed TM before (“digital users”), 27% were using VC as part of their TM expertise (“VC-users”), 10% stated to have experience with TM but not VC (“TM-users”). Those negating the use of any TM (62%) were designated as “digital non-users.” TM-Knowledge was self-rated as 4 [median on a Likert Scale 1 (very high) to 6 (very low)] with a significant difference between digital users (VC-user 2.7 ± 1.2, TM-user 3.2 ± 1.1) and digital non-users (4.4 ± 1.3). The reported significant increase of VC use during the lockdown periods and between the lockdowns compared to the pre-pandemic phase was regarded as a proxy for VC acceptance in the pandemic. Reasons for VC non-use were administrative/technical efforts (21%), lack of technical equipment (15%), time constraints (12%), time required for individual VC sessions (12%), inadequate reimbursement (11%), lack of demand from patients (11%), data security concerns (9%), poor internet connection (8%), and lack of scientific evaluation/evidence (5%). Physicians considered the following clinical situations to be particularly suitable for VC: follow-up visits (VC-user 79%, TM-user 62%, digital non-user 47%), emergency consultations (VC-user 20%, TM-user 33%, digital non-user 20%), and patients presenting for the first time (VC-user 11%, TM-user 19%, digital non-user 8%). Conclusion Even though the pandemic situation, with social distancing and several lockdowns, provides an ideal environment for the implementation of new remote care forms as VC, its use and acceptance remained comparatively low due to multiple reasons. This analysis may help identify hurdles in employing innovative digital care models for rheumatologic healthcare.